The The Role Of Indonesia's G20 Presidency In Global Environmental Governance - Latifah Ratu Dea; Wawan Budi Darmawan; Deasy Silvya Sari (GoAcademica Research & Publishing, 2026)
The buildup of global emissions in the Earth's atmosphere is making the problem of climate change more concerning. This has to do with how nations all over the globe are susceptible to the consequences of climate change brought on by greenhouse gas emissions. Countries are working together internationally to address these effects. During Indonesia's G20 Presidency in 2022, the G20 has made the energy transition a major topic of debate as a worldwide forum for the exchange of information and working together. Secondary sources provided the data for this study, which used qualitative research methodologies. In order to clarify Indonesia's G20 Presidency's significance in this domain, this paper also takes a global environmental governance stance. The study's findings show that the Just Energy Transition Partnership (JETP) and the Energy Transition Mechanism (ETM), two crucial agenda items for the advancement of global environmental governance in the energy sector, were produced in large part during the 2022 G20 meeting, of which Indonesia was either the host or the presidency. Keywords: Climate Change, Global Environmental Governance, Energy Transition, G20